Cystic lesion of pectoralis minor muscle - Javier García-Tirado; Marta Allué-Cabañuz; Nadia Muñoz-González; María Jesús Viso-Soriano; Isabel Marquina-Ibáñez (University of São Paulo, 2019)
Hydatidosis is a frequent infestation in large endemic areas, caused by helminths. Primary localization within the muscle or bone tissues is rare. We report the case of a 52-year-old woman with a cystic lesion located in the right pectoralis minor muscle, who was initially diagnosed with cystic lymphangioma by imaging examination. She was submitted for surgical treatment; in block resection of the tumor along with the involved muscle was performed. The histopathological diagnosis was of hydatid cyst. The contribution of the ancillary lab tests is analyzed for a precise preoperative diagnostic approach. This case well illustrates that the most likely is not always what it appears to be. Facing of a cystic lesion in the lungs, liver or muscle, clinicians should always think on hydatid disease, particularly in endemic areas.